2019
DOI: 10.1002/lno.11352
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of the microplankton community following a pulse of inorganic nitrogen in a eutrophic river

Abstract: Global change will increase the number and severity of extreme events resulting in strongly pulsed nutrient loading to rivers. Recent studies indicate the potential for rapid plankton shifts as short-term response to storm events and highlight the need for high-frequency methods to understand these complex processes. Here, we studied the effects of a strong short-term pulse of ammonium nitrate in a eutrophic temperate river that elevated nitrate-N concentrations from 3.1 to 10-55 mg L −1 . An intense phytoplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
(78 reference statements)
1
5
0
Order By: Relevance
“…For phytoplankton, we observed seasonal trends similar to those reported downstream in the Mississippi River (Baker & Baker, 1981) with diatoms being dominant during spring, Cyanobacteria dominant during summer, and that other taxa (e.g., green algae, cryptophytes) are present but rarely dominant. Similar seasonal succession of phytoplankton community structure has also been reported for eutrophic Minnesota lakes (Heiskary, Hirsch, & Rantala, 2016), and numerous other studies have documented seasonal succession of phytoplankton communities in lotic systems (e.g., Kleinteich et al, 2020;Peterson & Stevenson, 1989;Salmaso & Braioni, 2008;Tavernini et al, 2011). For zooplankton, community structure differed during May and October compared with other months, and several taxa groups, including rotifers, cyclopoids, copepodites, and nauplii were notably most abundant during May.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…For phytoplankton, we observed seasonal trends similar to those reported downstream in the Mississippi River (Baker & Baker, 1981) with diatoms being dominant during spring, Cyanobacteria dominant during summer, and that other taxa (e.g., green algae, cryptophytes) are present but rarely dominant. Similar seasonal succession of phytoplankton community structure has also been reported for eutrophic Minnesota lakes (Heiskary, Hirsch, & Rantala, 2016), and numerous other studies have documented seasonal succession of phytoplankton communities in lotic systems (e.g., Kleinteich et al, 2020;Peterson & Stevenson, 1989;Salmaso & Braioni, 2008;Tavernini et al, 2011). For zooplankton, community structure differed during May and October compared with other months, and several taxa groups, including rotifers, cyclopoids, copepodites, and nauplii were notably most abundant during May.…”
Section: Discussionsupporting
confidence: 77%
“…Chlorophyll-a is a component of phytoplankton that is often measured as a surrogate for phytoplankton biomass (e.g., Basu & Pick, 1996), and we accordingly observed increases in Chl-a associated with increases in phytoplankton biovolume, particularly for Chlorophyta and Cyanobacteria. Similarly, silica concentration declines because of uptake by diatoms, and typically increases following diatom blooms (Kleinteich et al, 2020;Tavernini et al, 2011). The Minnesota River is a fertile hypereutrophic system (Dodds, Jones, & Welch, 1998), and similar to many medium to large rivers, we suspect is rarely nutrient-limited (Salmaso & Braioni, 2008;Wehr & Descy, 1998).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Surplus N can also be stored as phycocyanin proteins and/or cyanophycin polymers in cyanobacteria (Boussiba & Richmond, 1980;Oliver et al, 2012) and more passively in phytoplankton cellular pools (Pedersen & Borum, 1996), but without a ubiquitous mechanism of active storage, increased transient uptake may be more coupled to water column concentrations of N (Stolte & Riegman, 1995). Phytoplankton culture experiments have shown diversity and plasticity in nutrient uptake kinetics (Cáceres et al, 2019;Suttle et al, 1987) such that estuarine and nearshore phytoplankton assemblages can rapidly uptake nutrients and augment biomass from short duration inputs (Cottingham et al, 2004;Kleinteich et al, 2020;Pinckney et al, 1999). Moreover, like our finding of an increase in U TDN / Chl a • PAR , McCarthy et al (2007) observed that water column NH x uptake rates increased with stormflow inputs of NH x to a rivermouth and nearshore area of Lake Erie (Old Woman Creek).…”
Section: Nitrogen and Phosphorusmentioning
confidence: 99%